Conservative Surgical Approach for Reduction of Macrocheilitis Caused by Massive Injection of Liquid Silicone. (January 2013) - Grippaudo, F.R.; Tammaro, A.; Narcisi, A.; Paolini, G.; Longo, B.; Falesiedi, F.; Santanelli, F.
Cosmetic lip augmentation, regardless of the filling agent, is nowadays one of the most requested aesthetic procedures. Liquid silicone injections were used in the past, but after reports of severe late complications their use has been discontinued, ending with a permanent ban in most western countries. In this report we describe clinical presentation, diagnostic pathways and surgical reconstruction of six patients presenting with macrocheilia due to previous liquid silicone augmentation. Patients showed chronic inflammation of the lower third of the face, lip eversion, various degrees of asymmetry and functional impairment of the lips. All patients underwent preoperative soft tissue High Frequency Ultrasound (HFUS) and Magnetic Resonance Imaging (MRI) of the of the face to obtain evidence of the filler material and to ascertain its diffusion within the soft tissues of the perioral region. Conservative surgery was carried out to remove foreign material and to restore symmetric aesthetically pleasing lips. Histology confirmed the siliconoma diagnosis. HFUS and RMI allowed to clearly identify the silicone within the soft tissues. The conservative surgery restored the harmonious relationship between the lips, with an improvement in lip functionality at long term follow-up. Healing was complete and uneventful in all of the patients.